IMPROVING READING SKILLS FOR THE UNIVERSITY ENTRANCE EXAMINATION FOR STUDENTS OF VOCATIONAL HIGH SCHOOL PELITA BANDUNG - Deden Novan Setiawan Nugraha; Dianita Dianita; Puspita Sari; Susiyanti Rusyan; Hero Gunawan (LPPM Univ. Ibn Khaldun Bogor, 2026)
This article reports the results of a community service program conducted at Vocational High School Pelita Bandung and its impact on students’ learning and motivation in the context of the Reading subject, as assessed through testing for English as a Foreign Language (EFL) learners. Two main aspects were examined: students’ perceptions of the exam, including attitude, content, methodology, course, and preparation, as well as students’ perceptions of their own motivation. Data were collected through observations of two classes and a questionnaire with 63 students representing four proficiency levels. The study found that students expressed positive rather than negative impact in both variables, namely learning and motivation, to the extent that it is appropriate for measuring their achievement goals. However, high-stakes testing still leaves some residual doubt regarding preparation. In terms of motivation, which encompasses content, methodology, and attitude, the results indicated a positive attitude that affects students’ development and helps them reach an optimal point on the test.